Special aggregate for low-steam-curing-energy-consumption light-weight high-strength concrete and preparation method of special aggregate

By using boron nitride ceramide in ultra-high performance concrete to absorb and store heat during curing, the problems of high energy consumption and drying shrinkage are solved, and the durability and engineering application benefits of concrete are improved.

CN119241271AInactive Publication Date: 2025-01-03CHINA CONSTR COMMERCIAL CONCRETE JIANGXI CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411324768.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-23
Publication Date
2025-01-03
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Ultra-high performance concrete has high energy consumption and drying shrinkage problems during steam curing, which affects its durability and engineering applications.

Method used

By mixing boron nitride material into the ceram, crushing and grinding, partially replace the natural fine aggregate of ultra-high performance concrete, the high thermal conductivity of boron nitride absorbs residual heat, and store heat through the ceram to avoid Heat unevenness and drying shrinkage enhance the mechanical properties and durability of concrete.

Benefits of technology

It effectively reduces the energy consumption of curing, reduces the risk of drying and shrinkage, improves the long-term mechanical properties and durability of concrete, and reduces production costs and natural resource consumption.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention discloses a special aggregate for low-steam-curing-energy-consumption light-weight high-strength concrete and a preparation method of the special aggregate, and belongs to the technical field of building materials. The aggregate is boron nitride lightweight aggregate, and the boron nitride lightweight aggregate comprises the following raw materials: shale, fly ash and boron nitride; the mass ratio of the shale to the fly ash is (85-92): (8-15); the dosage of the boron nitride is 3%-20% of the total mass of the shale and the fly ash. The boron nitride lightweight aggregate is prepared through aging, granulation, sintering, ball milling and screening and replaces part of natural aggregate to be used for preparing the concrete, and on the premise that the strength of the concrete is not affected, the maintenance energy consumption of the concrete can be obviously reduced, and the dead weight of the concrete can be reduced; meanwhile, the additive can be used as a self-curing agent to promote the long-term strength increase of concrete.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of building materials, and in particular to a special aggregate for low steam-curing energy consumption lightweight high-strength concrete and a preparation method thereof. Background Art

[0002] As the world's most widely used building material, concrete has been widely used in construction engineering and infrastructure due to its excellent compressive strength and working performance. However, since concrete is composed of various components, a large number of initial defects will inevitably form inside it during the mixing process, such as the interface transition zone between coarse aggregate and cement paste, which will reduce the durability under special conditions.

[0003] Ultra-High Performance Concrete (UHPC) is based on the theory of close particle packing. It often uses active powders such as silica fume and fly ash to fill the pores between cement stones to improve the internal density, greatly improving its mechanical properties and durability. It has the characteristics of high strength, high toughness, and high durability, and can be used in various harsh environments. However, UHPC itself has certain defects such as large deadweight and large shrinkage. For this reason, UHPC often uses steam or autoclave curing to reduce shrinkage creep, and give full play to the activity of its internal auxiliary cementitious materials to enhance its durability. But at the same time, another noteworthy problem arises, that is, the substantial increase in maintenance energy consumption and production costs, which is not conducive to the promotion and application of UHPC in actual engineering.

[0004] Therefore, the patent of the present invention proposes a special aggregate for lightweight high-strength concrete with low steam-curing energy consumption and a preparation method thereof. By adding boron nitride material into expanded clay, crushing and grinding it to partially replace the natural fine aggregate in UHPC, and using its high thermal conductivity to absorb the residual heat wasted by UHPC during steam curing, and storing the heat through expanded clay, it can effectively avoid the uneven heat inside UHPC caused by improper operation of construction personnel during the curing period, reduce the waste of curing energy, and reduce the risk of drying shrinkage of UHPC. At the same time, expanded clay can have a self-curing effect and enhance the long-term mechanical properties and durability of UHPC. Summary of the invention

[0005] In view of the deficiencies of the above prior art, the present invention provides a special aggregate for lightweight high-strength concrete with low steam-curing energy consumption and a preparation method thereof. The boron nitride material is added to ceramsite, which is crushed and ground to partially replace the natural fine aggregate in UHPC. The high thermal conductivity of the material is used to absorb the residual heat wasted by UHPC during steam curing, and the heat is stored in the ceramsite. The uneven heat inside the UHPC caused by improper operation of the construction personnel during the curing period can be effectively avoided, the waste of curing energy can be reduced, and the risk of drying shrinkage of UHPC can be reduced. At the same time, the ceramsite can have a self-curing effect, thereby enhancing the long-term mechanical properties and durability of UHPC.

[0006] To achieve the above purpose, the specific technical solutions of the present invention are as follows:

[0007] In a first aspect, the present invention provides a special aggregate for low steam-curing energy consumption lightweight high-strength concrete, wherein the aggregate is a boron nitride lightweight aggregate, and the raw materials of the boron nitride lightweight aggregate include: shale, fly ash, and boron nitride; the mass ratio of the shale to the fly ash is (85~92): (8~15); the amount of the boron nitride is 3%~20% of the total mass of the shale and the fly ash.

[0008] Preferably, the technical index of the boron nitride lightweight aggregate is: apparent density ≤ 1600 kg / m 3 ; Bulk density 700~800 kg / m 3 ; Fineness modulus 2.3~4.0; cylinder pressure strength ≥8 MPa; saturated water absorption (1 h) ≤10%.

[0009] Preferably, the boron nitride is one or a mixture of hexagonal boron nitride, cubic boron nitride or wurtzite boron nitride, and the particle size of the boron nitride is 5-50 μm, the purity is ≥99%, and the apparent density is 2300-3450 kg / m 3 .

[0010] Further preferably, the hexagonal boron nitride is prepared by one of the following three methods: reaction of borax with ammonium chloride, reaction of boric anhydride-tricalcium phosphate pellets with ammonia, reaction of borax with urea, and purification treatment is required after the reaction; the cubic boron nitride or wurtzite boron nitride is prepared by hexagonal boron nitride under high temperature and high pressure.

[0011] In a second aspect, the present invention provides a method for preparing the special aggregate for the low steam curing energy consumption lightweight high-strength concrete, comprising the following steps:

[0012] (1) The shale is crushed and ground to obtain powdered shale with a diameter less than 0.074 mm; the boron nitride is screened to obtain a powder with a particle size range of 5 to 20 μm;

[0013] (2) Mixing powdered shale and fly ash evenly, and then adding boron nitride powder and mixing evenly to obtain ceramsite raw material;

[0014] (3) Place the ceramsite raw material in a container, add an inorganic pore-forming agent and an appropriate amount of water, mix well, and age for 30 to 60 minutes;

[0015] (4) pelletizing the aged ceramsite raw material into balls and sintering them to obtain boron nitride ceramsite with a particle size ranging from 5 to 10 mm;

[0016] (5) The boron nitride ceramsite is ball-milled and sieved to obtain boron nitride lightweight aggregate with a particle size range of 0.075-4.75 mm.

[0017] Preferably, the specific operation of the sintering is as follows: placing the ceramsite raw material in an oven, controlling the temperature to 105±5°C, and drying for 30~40 min; placing the ceramsite raw material particles in a high-temperature furnace, adjusting the temperature to 400~500°C, and preheating for 20~30 min; adjusting the temperature to 1100~1200°C, sintering for 10~20 min, and then keeping warm for 15~20 min; reducing the temperature to room temperature at a rate of ≤3°C / min to obtain boron nitride ceramsite.

[0018] Preferably, the SiO2 content in the shale is 40%~70%, and the Al2O3 content is 11%~25%.

[0019] Preferably, the ball mill used for the ball milling is one of a cone ball mill, an ultrafine layered mill or an energy-saving ball mill.

[0020] Preferably, the fly ash is Class F, Grade II fly ash recovered from a coal-fired power plant, and its particle size is ≤0.9 mm.

[0021] Preferably, the airflow sieving device used for the sieving can generate an airflow of 30 to 120 m 3 / h, the speed is 5~30rpm, and the screen can be cleaned automatically at the same time.

[0022] Preferably, the water is tap water for urban life.

[0023] Preferably, the inorganic pore-forming agent is one or a mixture of carbon powder, calcium carbonate or magnesium carbonate.

[0024] Preferably, the amount of the inorganic pore-forming agent is 6% to 8% of the mass of the ceramsite raw material.

[0025] Preferably, the moisture content of the aged ceramsite raw material is 10% to 15%.

[0026] Preferably, the container is an iron cylindrical container with a wall thickness of 10 to 20 mm.

[0027] Preferably, the granulator used for granulation into balls is one of a double-die extrusion granulator, a pot granulator or a rotary granulator.

[0028] In a third aspect, the present invention provides a lightweight, high-strength concrete with low steam-curing energy consumption. The raw materials include, by weight: 650-800 parts of cement, 150-200 parts of fly ash, 150-200 parts of silica fume, 200-480 parts of boron nitride lightweight aggregate, 0-400 parts of sand, 156-195 parts of steel fiber, 150-250 parts of water, and 20-30 parts of admixture.

[0029] In a fourth aspect, the present invention provides a method for preparing the lightweight and high-strength concrete with low steam curing energy consumption, comprising the following steps:

[0030] S1. Pre-wet the boron nitride lightweight aggregate for 1-2 h;

[0031] S2, adding cement, sand, fly ash and silica fume into a concrete mixer in sequence and mixing them evenly;

[0032] S3, adding boron nitride lightweight aggregate into a concrete mixer and mixing evenly;

[0033] S4, adding the admixture into water, mixing evenly, pouring into a concrete mixer, mixing evenly, and then adding steel fiber in small amounts several times until completely mixed to obtain a mixture;

[0034] S5. Pour the mixture into the mold, vibrate and shape it, steam cure it for 20-30 hours, then switch to standard curing for 28-56 days, remove the mold, and obtain lightweight and high-strength concrete.

[0035] Preferably, the cement is ordinary Portland cement of P·O 52.5 grade, with a specific surface area of ​​≥375 m 2 / kg.

[0036] Preferably, the silica fume is grade 90 silica fume, with a particle size of ≤0.2 μm, a SiO2 content of ≥90%, a loss on ignition of ≤3.0%, and a specific surface area of ​​≥20,000 m 2 / kg.

[0037] Preferably, the fly ash is Class F Grade I fly ash microbeads, with a particle size of ≤0.9 mm and a specific surface area of ​​≥1300 m 2 / kg, sphere density ≤2300 kg / m 3 , water requirement ratio ≤95%.

[0038] Preferably, the sand is quartz sand with a fineness modulus of 1.6-2.2 and an apparent density of about 2550-2650 kg / m 3 .

[0039] Preferably, the steel fiber is a straight copper-plated microfilament steel fiber with a length of 10-13 mm, a diameter of 0.2-0.3 mm, and an apparent density of 7800-7850 kg / m 3 , elastic modulus is 200~220 GPa, and tensile strength is ≥2500 MPa.

[0040] Preferably, the admixture is a polycarboxylic acid high-efficiency water reducer with a solid content of 40% to 50% and a water reduction rate of ≥30%.

[0041] Preferably, the water is tap water for urban life.

[0042] Preferably, the temperature of the steam curing is 85-90°C, the relative humidity is ≥95%, the enclosure structure is covered with canvas for curing or cured in a vertical curing bin; the thermal conductivity of the canvas is ≤0.23W / (m·K), and the vertical curing bin is made of steel-polyurethane material, and its thermal conductivity is ≤0.024W / (m·K).

[0043] Compared with the prior art, the present invention is beneficial in that:

[0044] (1) After the boron nitride lightweight aggregate provided by the present invention is used to prepare lightweight high-strength concrete, the high thermal conductivity of boron nitride can be used to absorb the residual heat that escapes from the lightweight high-strength concrete due to improper operation of construction workers during steam curing, and the high thermal insulation of the ceramsite in the outer layer of the aggregate can be used to effectively store the residual heat; a large amount of boron nitride lightweight aggregate is evenly distributed inside the lightweight high-strength concrete to form a dense temperature storage network, which can significantly reduce the curing heat loss of the lightweight high-strength concrete, improve the steam curing energy consumption ratio, effectively reduce the curing cost of the lightweight high-strength concrete and improve the drying shrinkage phenomenon of the lightweight high-strength concrete, thereby achieving the purpose of improving the production efficiency of concrete.

[0045] (2) The boron nitride lightweight aggregate provided by the present invention has good porosity. After being pre-wetted and used in lightweight high-strength concrete, it can provide moisture for cement hydration reaction in areas that are difficult for steam to reach, ensure the balance and stability of internal humidity in the early stage, and make the hydration reaction in various parts of the lightweight high-strength concrete maintain coordination, effectively improving the pore structure distribution of the lightweight high-strength concrete; in addition, after the steam curing of the lightweight high-strength concrete is completed, the boron nitride lightweight aggregate can continue to release moisture slowly, react with the cement particles that have not yet been hydrated, and promote the growth of the strength of the lightweight high-strength concrete in the later stage.

[0046] (3) The boron nitride lightweight aggregate provided by the present invention has low density and high strength. When used to prepare concrete, the obtained lightweight high-strength concrete can significantly reduce its own weight while ensuring that the strength is not lost, thereby improving the mechanical properties of the lightweight high-strength concrete structure, which has obvious engineering significance.

[0047] (4) The present invention partially replaces the fine aggregate in the lightweight high-strength concrete with boron nitride lightweight aggregate in proportion, which can reduce the engineering cost required for mining natural fine aggregate and reduce the consumption of natural resources, which has significant environmental significance. DETAILED DESCRIPTION

[0048] The technical solution of the present invention will be described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0049] The present invention provides a special aggregate for low steam-curing energy consumption lightweight high-strength concrete. The aggregate is a boron nitride light aggregate. The raw materials of the boron nitride light aggregate include: shale, fly ash, and boron nitride. The mass ratio of the shale to the fly ash is (85-92): (8-15). The amount of the boron nitride is 3%-20% of the total mass of the shale and the fly ash.

[0050] In some examples, the technical indicators of the boron nitride lightweight aggregate are: apparent density ≤ 1600 kg / m 3 ; Bulk density 700~800 kg / m 3 ; Fineness modulus 2.3~4.0; cylinder pressure strength ≥8 MPa; saturated water absorption (1 h) ≤10%.

[0051] In some examples, the boron nitride is one or a mixture of hexagonal boron nitride, cubic boron nitride or wurtzite boron nitride, and the particle size of the boron nitride is 5-50 μm, the purity is ≥99%, and the apparent density is 2300-3450 kg / m 3 .

[0052] The method for preparing the boron nitride lightweight aggregate comprises the following steps:

[0053] (1) The shale is crushed and ground to obtain powdered shale with a diameter less than 0.074 mm; the boron nitride is screened to obtain a powder with a particle size range of 5 to 20 μm;

[0054] (2) Mixing powdered shale and fly ash evenly, and then adding boron nitride powder and mixing evenly to obtain ceramsite raw material;

[0055] (3) Place the ceramsite raw material in a container, add an inorganic pore-forming agent and an appropriate amount of water, mix well, and age for 30 to 60 minutes;

[0056] (4) pelletizing the aged ceramsite raw material into balls and sintering them to obtain boron nitride ceramsite with a particle size ranging from 5 to 10 mm;

[0057] (5) The boron nitride ceramsite is ball-milled and sieved to obtain boron nitride lightweight aggregate with a particle size range of 0.075-4.75 mm.

[0058] In some examples, the ball mill used for the ball milling is one of a cone ball mill, an ultrafine layered mill, or an energy-saving ball mill.

[0059] In some examples, the inorganic pore former is one or a mixture of carbon powder, calcium carbonate or magnesium carbonate.

[0060] In some examples, the amount of the inorganic pore former is 6% to 8% of the mass of the ceramsite raw material.

[0061] In some examples, the moisture content of the aged ceramsite raw material is 10% to 15%.

[0062] In some examples, the granulator used for the granulation into balls is a double-die extrusion granulator, a pan granulator or a rotary granulator.

[0063] In the following specific examples, the content of SiO2 in the shale is 63.27%, and the content of Al2O3 is 15.04%; the ball mill used for the ball milling is a conical ball mill; the fly ash is Class F II fly ash recovered from a coal-fired power plant, and its particle size is ≤0.9 mm; the boron nitride is hexagonal boron nitride, with a particle size of 5-50 μm, a purity of 99%, and an apparent density of 2300 kg / m 3 , prepared by the reaction of borax and ammonium chloride, and purified to a purity of 99% after the reaction is completed; the air flow sieving device used for the screening can generate an air flow of 30~120 m 3 / h, the rotation speed is 5-30 rpm, and the screen can be automatically cleaned at the same time; the water is tap water for urban life; the inorganic pore-forming agent is calcium carbonate, and the dosage is 7% of the mass of the ceramsite raw material; the moisture content of the ceramsite raw material after aging is 10%; the container is an iron cylindrical container with a wall thickness of 10-20 mm; the granulator used for granulation and balling is a double-die extrusion granulator.

[0064] The present invention also provides a lightweight high-strength concrete with low steam curing energy consumption. The raw materials include, by weight: 650-800 parts of cement, 150-200 parts of fly ash, 150-200 parts of silica fume, 200-480 parts of boron nitride lightweight aggregate, 0-400 parts of sand, 156-195 parts of steel fiber, 150-250 parts of water, and 20-30 parts of admixture.

[0065] The method for preparing the lightweight and high-strength concrete with low steam curing energy consumption comprises the following steps:

[0066] S1. Pre-wet the boron nitride lightweight aggregate for 1-2 h;

[0067] S2, adding cement, sand, fly ash and silica fume into a concrete mixer in sequence and mixing them evenly;

[0068] S3, adding boron nitride lightweight aggregate into a concrete mixer and mixing evenly;

[0069] S4, adding the admixture into water, mixing evenly, pouring into a concrete mixer, mixing evenly, and then adding steel fiber in small amounts several times until completely mixed to obtain a mixture;

[0070] S5. Pour the mixture into the mold, vibrate and shape it, steam cure it for 20-30 hours, then switch to standard curing for 28-56 days, remove the mold, and obtain lightweight and high-strength concrete.

[0071] In the following specific examples, the cement is ordinary Portland cement of P·O 52.5 grade, with a specific surface area of ​​380 m 2 / kg; the silica fume is grade 90 silica fume, with a particle size of ≤0.2 μm, a SiO2 content of 92%, a loss on ignition of ≤2.0%, and a specific surface area of ​​21000 m 2 / kg; the fly ash is Class F, Class I fly ash microspheres, with a particle size of ≤0.9 mm and a specific surface area of ​​1300 m 2 / kg, the density of the sphere is 2300 kg / m 3 , the water requirement ratio is 90%; the sand is quartz sand, the fineness modulus is 2.0, and the apparent density is about 2600 kg / m 3 The steel fiber is a straight copper-plated microfilament steel fiber with a length of 13 mm, a diameter of 0.2 mm, and an apparent density of 7800 kg / m 3 , elastic modulus is 220 GPa, and tensile strength is 2700 MPa; the admixture is polycarboxylic acid high-efficiency water-reducing agent with a solid content of 40% and a water reduction rate of ≥30%; the water is tap water for urban life; the steam curing temperature is 90°C, the relative humidity is 95%, and the enclosure structure is covered with canvas for curing, and the thermal conductivity of the canvas is 0.23W / (m·K).

[0072] Example 1

[0073] A special aggregate for low steam curing energy consumption lightweight high-strength concrete, the preparation steps are as follows:

[0074] (1) The shale is crushed and ground to obtain powdered shale with a diameter less than 0.074 mm; the boron nitride is screened to obtain a powder with a particle size range of 5 to 20 μm;

[0075] (2) Powdered shale and fly ash are mixed in a mass ratio of 92:8, and then boron nitride is added in an amount of 20% of the total mass of the powdered shale and fly ash, and the mixture is mixed evenly to obtain ceramsite raw material;

[0076] (3) Pour the ceramsite raw material into a rigid container, add an inorganic pore-forming agent and an appropriate amount of water and stir until the mixture is uniformly mixed. After the stirring is completed, the ceramsite raw material is placed in the container for aging for 60 min;

[0077] (4) The aged ceramsite raw material is pelletized into balls, and the ceramsite raw material particles are placed in an oven, the oven temperature is controlled to be 105±5℃, and the ceramsite raw material particles are dried for 30 minutes; then, the ceramsite raw material particles are placed in a high-temperature furnace, the temperature is adjusted to 500℃, and the ceramsite raw material particles are preheated for 20 minutes; after the preheating is completed, the temperature in the furnace is adjusted to 1150℃ to sinter the ceramsite raw material for 20 minutes, and then the temperature is kept at 20 minutes, and then the temperature in the furnace is controlled to cool at a rate of 3℃ / min, and after cooling to room temperature, boron nitride ceramsite is prepared;

[0078] (5) The boron nitride ceramsite is ball-milled and then sieved using an airflow sieving instrument to obtain a boron nitride lightweight aggregate with a particle size range of 0.075 to 4.75 mm. The technical indicators of the boron nitride lightweight aggregate are shown in Table 1.

[0079] Table 1: Technical indicators of boron nitride lightweight aggregate

[0080]

[0081] Example 2

[0082] A lightweight high-strength concrete with low steam curing energy consumption, the raw materials include, by weight: 670 parts of cement, 150 parts of fly ash, 150 parts of silica fume, 220 parts of boron nitride lightweight aggregate, 380 parts of sand, 156 parts of steel fiber, 190 parts of water, and 24 parts of admixture, and the preparation steps are as follows:

[0083] S1. Pre-wetting the boron nitride lightweight aggregate prepared in Example 1 for 2 h;

[0084] S2. Add cement, sand, fly ash and silica fume into a concrete mixer in sequence and stir for 3 minutes to mix well;

[0085] S3, adding the pre-wetted boron nitride lightweight aggregate into a concrete mixer and stirring for 2 minutes to mix evenly;

[0086] S4. Add the admixture to water, mix well, pour into a concrete mixer, stir for 2 minutes to mix well, then add steel fiber in small amounts several times until it is completely mixed to obtain a mixture;

[0087] S5. Pour the mixture into the mold, vibrate and shape it, steam cure it for 24 h, then switch to standard curing for 28 d, remove the mold, and obtain a lightweight high-strength concrete, named A1.

[0088] Example 3

[0089] A lightweight high-strength concrete with low steam curing energy consumption, the raw materials include, by weight: 670 parts of cement, 150 parts of fly ash, 150 parts of silica fume, 480 parts of boron nitride lightweight aggregate, 0 parts of sand, 156 parts of steel fiber, 190 parts of water, and 24 parts of admixture, and the preparation steps are as follows:

[0090] S1. Pre-wetting the boron nitride lightweight aggregate prepared in Example 1 for 2 h;

[0091] S2. Add cement, fly ash and silica fume into a concrete mixer in sequence and stir for 3 minutes to mix well;

[0092] S3, adding the pre-wetted boron nitride lightweight aggregate into a concrete mixer and stirring for 2 minutes to mix evenly;

[0093] S4. Add the admixture to water, mix well, pour into a concrete mixer, stir for 2 minutes to mix well, then add steel fiber in small amounts several times until it is completely mixed to obtain a mixture;

[0094] S5. Pour the mixture into the mold, vibrate and shape it, steam cure it for 24 h, then switch to standard curing for 28 d, remove the mold, and obtain a lightweight and high-strength concrete, named A2.

[0095] Comparative Example 1

[0096] A high-strength concrete, the raw materials include by weight: 670 parts of cement, 150 parts of fly ash, 150 parts of silica fume, 750 parts of sand, 156 parts of steel fiber, 190 parts of water, and 26 parts of admixture, and the preparation steps are as follows:

[0097] (1) Add cement, sand, fly ash and silica fume into a concrete mixer in sequence and stir for 3 minutes until they are evenly mixed;

[0098] (2) Add the admixture to water, mix well, then pour into a concrete mixer and stir for 2 minutes to mix well. Then add steel fiber in small amounts several times until it is completely mixed to obtain a mixture.

[0099] (3) The mixture was poured into the mold, vibrated and formed, and then steam-cured for 24 h. Then, it was switched to standard curing for 28 d. The mold was removed to obtain concrete, which was named KB.

[0100] Comparative Example 2

[0101] A lightweight high-strength concrete, named B1, is prepared in the same steps as in Example 2, except that an equal amount of lightweight aggregate is used to replace the boron nitride lightweight aggregate, that is, the raw materials include, by weight: 670 parts of cement, 150 parts of fly ash, 150 parts of silica fume, 220 parts of lightweight aggregate, 380 parts of sand, 156 parts of steel fiber, 190 parts of water, and 24 parts of admixture. The lightweight aggregate is prepared by the following method:

[0102] (1) crushing and grinding the shale to obtain powdered shale with a diameter less than 0.074 mm;

[0103] (2) mixing powdered shale and fly ash in a mass ratio of 92:8 to obtain ceramsite raw material;

[0104] (3) Pour the ceramsite raw material into a rigid container, add an inorganic pore-forming agent and an appropriate amount of water and stir until the mixture is uniformly mixed. After the stirring is completed, the ceramsite raw material is placed in the container for aging for 60 min;

[0105] (4) The aged ceramsite raw material is pelletized into balls, and the ceramsite raw material particles are placed in an oven, the oven temperature is controlled to be 105±5℃, and the ceramsite raw material particles are dried for 30 minutes; then, the ceramsite raw material particles are placed in a high-temperature furnace, the temperature is adjusted to 500℃, and the ceramsite raw material particles are preheated for 20 minutes; after the preheating is completed, the temperature in the furnace is adjusted to 1150℃ to sinter the ceramsite raw material for 20 minutes, and then the temperature is kept at this temperature for 20 minutes, and then the temperature in the furnace is controlled to cool at a rate of 3℃ / min, and after cooling to room temperature, ceramsite is prepared;

[0106] (5) The expanded clay is ball-milled and then sieved using an air flow sieving device to obtain lightweight aggregate with a particle size range of 0.075 to 4.75 mm.

[0107] Comparative Example 3

[0108] A lightweight high-strength concrete, named B2, includes raw materials by weight: 670 parts of cement, 150 parts of fly ash, 150 parts of silica fume, 220 parts of boron nitride lightweight aggregate, 380 parts of sand, 156 parts of steel fiber, 190 parts of water, and 24 parts of admixture. The preparation steps are basically the same as those in Example 2, except that the boron nitride lightweight aggregate used is prepared by the following method:

[0109] (1) The shale is crushed and ground to obtain powdered shale with a diameter less than 0.074 mm; the boron nitride is screened to obtain a powder with a particle size range of 5 to 20 μm;

[0110] (2) Powdered shale and fly ash are mixed in a mass ratio of 92:8, and then boron nitride is added in an amount of 25% of the total mass of the powdered shale and fly ash, and the mixture is mixed evenly to obtain ceramsite raw material;

[0111] (3) Pour the ceramsite raw material into a rigid container, add an inorganic pore-forming agent and an appropriate amount of water and stir until the mixture is uniformly mixed. After the stirring is completed, the ceramsite raw material is placed in the container for aging for 60 min;

[0112] (4) The aged ceramsite raw material is pelletized into balls, and the ceramsite raw material particles are placed in an oven, the oven temperature is controlled to be 105±5℃, and the ceramsite raw material particles are dried for 30 minutes; then, the ceramsite raw material particles are placed in a high-temperature furnace, the temperature is adjusted to 500℃, and the ceramsite raw material particles are preheated for 20 minutes; after the preheating is completed, the temperature in the furnace is adjusted to 1150℃ to sinter the ceramsite raw material for 20 minutes, and then the temperature is kept at 20 minutes, and then the temperature in the furnace is controlled to cool at a rate of 3℃ / min, and after cooling to room temperature, boron nitride ceramsite is prepared;

[0113] (5) The boron nitride ceramsite is ball-milled and then sieved using an air flow sieving instrument to obtain boron nitride lightweight aggregate with a particle size range of 0.075 to 4.75 mm.

[0114] The energy consumption of equipment for each group of concrete during steam curing was recorded and converted into standard coal consumption. The results are shown in Table 2.

[0115] Table 2: Average curing energy consumption of each group of concrete

[0116]

[0117] As shown in Table 2, the average curing energy consumption of group A1 is about 8.2% lower than that of group KB; when the amount of boron nitride light aggregate is increased to completely replace natural sand, the average curing energy consumption of group A2 can be reduced by about 17.6% compared with group KB. After adding boron nitride light aggregate, the average curing energy consumption of single cubic meter concrete has been significantly reduced, which effectively saves the curing resources of lightweight high-strength concrete and saves engineering construction costs. In addition, the average curing energy consumption of group B1 increased by about 7.7% compared with group A1, but was still about 1.1% lower than that of group KB, indicating that the single-mixed ceramsite light aggregate has a certain heat absorption and heat preservation effect. However, due to the lack of boron nitride, the curing energy consumption reduction effect of ceramsite light aggregate has been significantly attenuated. The average curing energy consumption of group B2 is about 4.8% lower than that of group A1. A higher amount of boron nitride can provide more efficient paths for the inward transfer of curing heat, thereby reducing the curing escape heat and improving the steam curing efficiency of concrete.

[0118] After the curing is completed, the dry apparent density of each group of concrete is measured; and, referring to the "Standard for Test Methods for Physical and Mechanical Properties of Concrete" (GB / T 50081-2019), the compressive strength of each group of concrete at different ages is tested, and the results are shown in Table 3.

[0119] Table 3: Dry apparent density of concrete in each group and compressive strength at each age

[0120]

[0121] It can be seen from Table 3 that the dry apparent density of the lightweight high-strength concrete of the present invention is 2128~2241 kg / m 3 , showing good lightweight characteristics, which can significantly reduce the deadweight of concrete; in addition, with the increase of the content of boron nitride lightweight aggregate, its dry apparent density gradually decreases. At each age, the compressive strength of group A1 and group A2 is slightly higher than that of KB. This is because the boron nitride lightweight aggregate has a porous structure. When pre-wetted, its surface can absorb a small amount of water. After being evenly mixed into the concrete, it can release water for a long time and slowly for the cementitious material in the vicinity, promote the formation of hydration reaction, and play the role of a self-curing agent. The compressive strength of group B1 at each age is slightly lower than that of group A1. This is because the ceramsite lightweight aggregate is not mixed with boron nitride powder, and its overall physical properties are poor compared with those of boron nitride lightweight aggregate, which affects the development of concrete compressive strength. The 7d, 28d and 56d compressive strengths of group B2 were 5.5MPa, 4.5MPa and 4.7MPa lower than those of group A1, respectively. This is mainly because when the boron nitride dosage is high, the dispersion of boron nitride powder in the expanded clay granulation process is poor and it is easy to agglomerate, resulting in a decrease in the overall physical properties of the boron nitride lightweight aggregate, which is not conducive to the compressive strength of concrete.

[0122] In summary, the present invention uses shale, fly ash and boron nitride as raw materials, and adopts aging, granulation, sintering, ball milling and screening to prepare boron nitride light aggregate. After partially or completely replacing natural sand and adding it into concrete, it can significantly reduce the maintenance energy consumption of concrete and reduce the deadweight of concrete without affecting the strength of concrete; at the same time, boron nitride light aggregate can be used as a self-curing agent to promote the strength growth of concrete. The present invention uses boron nitride light aggregate to partially replace natural aggregate, which can reduce the use of natural aggregate, reduce the exploitation of natural resources, and provide more superior green building materials for structural design in the fields of large-span bridges, high-rise buildings, etc.

[0123] The above specific embodiments describe the implementation of the present invention in detail, but the present invention is not limited to the specific details in the above embodiments. Within the scope of the claims and technical concept of the present invention, the technical solution of the present invention can be modified and changed in many simple ways, and these simple modifications all belong to the protection scope of the present invention.

Claims

1. A special aggregate for low steam curing energy consumption lightweight high strength concrete, characterized in that: The aggregate is boron nitride light aggregate, and the raw materials of the boron nitride light aggregate include: shale, fly ash, and boron nitride; the mass ratio of the shale to the fly ash is (85-92): (8-15); the amount of the boron nitride is 3%-20% of the total mass of the shale and the fly ash.

2. The special aggregate for low steam curing energy consumption lightweight high strength concrete according to claim 1, characterized in that: The technical index of the boron nitride lightweight aggregate is: apparent density ≤ 1600 kg / m 3 ; Bulk density 700~800 kg / m 3 ; Fineness modulus 2.3~4.0; cylinder pressure strength ≥8 MPa; saturated water absorption ≤10%.

3. The special aggregate for low steam curing energy consumption lightweight high strength concrete according to claim 1, characterized in that: The boron nitride is one or a mixture of hexagonal boron nitride, cubic boron nitride or wurtzite boron nitride. The particle size of the boron nitride is 5-50 μm, the purity is ≥99%, and the apparent density is 2300-3450 kg / m 3 .

4. A method for preparing a special aggregate for low steam curing energy consumption lightweight high-strength concrete, characterized in that: The following steps are involved: (1) The shale is crushed and ground to obtain powdered shale with a diameter less than 0.074 mm; the boron nitride is screened to obtain a powder with a particle size range of 5 to 20 μm; (2) Mixing powdered shale and fly ash evenly, and then adding boron nitride powder and mixing evenly to obtain ceramsite raw material; (3) Place the ceramsite raw material in a container, add an inorganic pore-forming agent and an appropriate amount of water, mix well, and age; (4) pelletizing the aged ceramsite raw material into balls and sintering them to obtain boron nitride ceramsite with a particle size ranging from 5 to 10 mm; (5) The boron nitride ceramsite is ball-milled and sieved to obtain boron nitride lightweight aggregate with a particle size range of 0.075-4.75 mm.

5. The method for preparing a special aggregate for low steam curing energy consumption lightweight high-strength concrete according to claim 4, characterized in that: The aging time is 30 to 60 min.

6. The method for preparing a special aggregate for low steam curing energy consumption lightweight high strength concrete according to claim 4, characterized in that: The specific operation of sintering is as follows: placing the ceramsite raw material in an oven, controlling the temperature to 105±5°C, and drying for 30-40 min; placing the ceramsite raw material particles in a high-temperature furnace, adjusting the temperature to 400-500°C, and preheating for 20-30 min; adjusting the temperature to 1100-1200°C, sintering for 10-20 min, and then keeping warm for 15-20 min; reducing the temperature to room temperature at a rate of ≤3°C / min to obtain boron nitride ceramsite.

7. A low steam curing energy consumption lightweight high strength concrete, characterized in that: The raw materials include, by weight: 650-800 parts of cement, 150-200 parts of fly ash, 150-200 parts of silica fume, 200-480 parts of boron nitride lightweight aggregate, 0-400 parts of sand, 156-195 parts of steel fiber, 150-250 parts of water, and 20-30 parts of admixture.

8. The method for preparing a low steam curing energy consumption lightweight high strength concrete according to claim 7, characterized in that: The following steps are involved: S1. Pre-wetting the boron nitride lightweight aggregate; S2, adding cement, sand, fly ash and silica fume into a concrete mixer in sequence and mixing them evenly; S3, adding boron nitride lightweight aggregate into a concrete mixer and mixing evenly; S4, adding the admixture into water, mixing evenly, pouring into a concrete mixer, mixing evenly, and then adding steel fiber in small amounts several times until completely mixed to obtain a mixture; S5. Pour the mixture into the mold, vibrate and shape it, steam cure it for 20-30 hours, then switch to standard curing for 28-56 days, remove the mold, and obtain lightweight and high-strength concrete.

9. The method for preparing a lightweight high-strength concrete with low steam curing energy consumption according to claim 8, characterized in that: The pre-wetting treatment time is 1 to 2 h.

10. The method for preparing a lightweight high-strength concrete with low steam curing energy consumption according to claim 8, characterized in that: The temperature of the steam curing is 85-90°C, the relative humidity is ≥95%, the enclosure structure of the steam curing is covered with canvas for curing or cured in a vertical curing bin; the thermal conductivity of the canvas is ≤0.23W / (m·K), the vertical curing bin is made of steel-polyurethane material, and the thermal conductivity of the steel-polyurethane material is ≤0.024W / (m·K).

Citation Information

Cited By

  • Temperature self-balancing fine aggregate concrete and preparation method thereof

    CN119930226A

  • A temperature self-balancing fine stone concrete and a preparation method thereof

    CN119930226B